Differential Expression of Claudin-3 and Claudin-1 in Mycosis Fungoides: Implications for Disease Monitoring - Aktaş, Akın; Erduran, Funda; Tuğrul, Burcu; Eren, Funda; Fırat Oğuz, Esra (Dermatology Practical & Conceptual, 2025)
Introduction: Claudins are integral transmembrane proteins that play a pivotal role in regulating tight junctions within epithelial and endothelial cells. In addition to their fundamental function in preserving cell-cell adhesion and barrier integrity, claudins are implicated in various biological processes, including those critical to cancer development and dermatological disorders. However, the role of claudin-1 and claudin-3 in mycosis fungoides (MF) pathogenesis remains unexplored and has yet to be comprehensively studied. Objectives: This study aimed to investigate the serum levels of claudin-1 and claudin-3 in MF patients and assess their potential clinical significance as biomarkers for disease progression. Methods: A total of 88 MF patients and 88 healthy controls were included in this case-control study. Serum claudin-1 and claudin-3 levels were measured using enzyme-linked immunosorbent assay (ELISA). Statistical analyses were performed to compare claudin levels between groups and examine correlations with disease stage and duration. Results: Serum claudin-3 levels were significantly higher in MF patients compared to controls (P<0.001), while no significant difference was observed in claudin-1 levels (P=0.448). Additionally, a weak but statistically significant positive correlation was found between claudin-3 levels and MF stage (r=0.219, P=0.041), suggesting its potential role in disease progression. No significant correlation was observed between claudin-1 levels and MF stage. Conclusion: Our findings indicate that elevated serum claudin-3 levels are associated with MF and correlate with disease severity, suggesting that claudin-3 may serve as a valuable biomarker for monitoring disease progression. Further research is required to elucidate its underlying mechanisms and assess its potential as a therapeutic target in MF.